2014
DOI: 10.1177/2325967114544107
|View full text |Cite
|
Sign up to set email alerts
|

Current Physical and Mental Health of Former Collegiate Athletes

Abstract: Background:There is a dearth of research on the current health of former collegiate athletes.Purpose:To examine the current health and related correlates in a cohort of former collegiate athletes who played in a diverse range of men’s and women’s sports with various levels of contact.Study Design:Cross-sectional study; Level of evidence, 3.Methods:Former collegiate athletes (N = 3657) were asked to complete an online questionnaire addressing sports history, medical history, and demographics. The questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 32 publications
(54 reference statements)
4
66
1
1
Order By: Relevance
“…Didehbani and colleagues studied cognitively intact former NFL athletes and found greater depression symptoms compared with age and intelligence quotient (IQ)-matched subjects 35. In a sample of 797 former collegiate athletes (all sports), approximately 39% of whom reported one or more prior concussions, their rates of self-reported mental health and cognitive problems were as follows: depression=10.4%, anxiety=16.2%, alcohol dependence=5.8%, substance use=2.9% and cognitive problems=3.8% 30. This sample also completed the Patient Health Questionnaire-9 (PHQ-9) to screen for depression.…”
Section: Resultsmentioning
confidence: 99%
“…Didehbani and colleagues studied cognitively intact former NFL athletes and found greater depression symptoms compared with age and intelligence quotient (IQ)-matched subjects 35. In a sample of 797 former collegiate athletes (all sports), approximately 39% of whom reported one or more prior concussions, their rates of self-reported mental health and cognitive problems were as follows: depression=10.4%, anxiety=16.2%, alcohol dependence=5.8%, substance use=2.9% and cognitive problems=3.8% 30. This sample also completed the Patient Health Questionnaire-9 (PHQ-9) to screen for depression.…”
Section: Resultsmentioning
confidence: 99%
“…53 A recent study showed that 44.4% of former Division 1 NCAA athletes 22 to 51 years of age from the same university were overweight or obese. 54 Nutrition knowledge has been positively associated with better diet quality among athletes. 55 The exploration of culinary attitudes, culinary confidence, and barriers to cooking among college athletes is limited.…”
Section: College Athlete Cooking Skills and Barriers To Cookingmentioning
confidence: 99%
“…32 Again, there are numerous findings that suggest frequent intake of fast food can lead to poor diet quality, 33 weight gain and insulin resistance, 34 and a higher BMI 35 and former athletes are no exception. 54…”
Section: Culinarymentioning
confidence: 99%
“…Existing sport injury risk assessment literature (Hawkins & Fuller, ; Maffulli et al., ; Freckleton & Pizzari, ), along with longitudinal injury surveillance and epidemiological data (Hootman et al., ; Doherty et al., ; Palmer‐Green et al., ), demonstrates that sport injuries are common among athletes across levels of competition. Sport injuries can elicit a range of psychological consequences to the injured athletes (Wiese‐Bjornstal et al., ; Galambos et al., ; Wiese‐Bjornstal, ; Kamphoff et al., ), which may in turn impact their return to play decisions (Podlog et al., ; Shrier, ), long‐term health and well‐being (Kerr et al., ; Roessler et al., ), and in the case of student‐athletes, academic progression (Klieber & Brock, ; Moreau et al., ). Despite research advancements made regarding the psychological consequences of sport injury, surprisingly little is known about the psychological factors associated with injury occurrence (Appaneal & Habif, ).…”
Section: Perceived Susceptibility To Sport Injury Items and Scoringmentioning
confidence: 99%